The house on the cliff - Dixon, Franklin W. (1987)
Teenage detectives Frank and Joe Hardy investigate a supposedly haunted house reported to be the hangout of criminals.
Keywords: Detective and mystery stories; Hardy Boys (Fictitious characters) -- Juvenile fiction